1994
DOI: 10.1002/mats.1994.040030408
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of phase separations of block copolymers and of corresponding blends

Abstract: SUMMARY:The Monte Carlo method has been used to simulate the phase separations of block copolymers and of corresponding blends with very high concentration (sum of volume fractions of blocks A and B: @A + GB = 0,9545). Our main findings are as follows: (1) The mixing is nonrandom even in the athermal limit. (2) The nonselective good solvent molecules = 0,0455) are mostly located at the interface between A-and B-rich phases, thus, it is not true that solvent and monomeric units will remain mixed at all temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…10, the correlation functions defined by Eqs. (11)- (14) are shown for the random and diblock copolymer systems, each at high and low temperatures. At high temperatures both systems behave like a homogeneous melt.…”
Section: Diblock Randommentioning
confidence: 99%
“…10, the correlation functions defined by Eqs. (11)- (14) are shown for the random and diblock copolymer systems, each at high and low temperatures. At high temperatures both systems behave like a homogeneous melt.…”
Section: Diblock Randommentioning
confidence: 99%
“…In the simulation, standard periodic boundary condition has been imposed on the lattice to mimic an infinite-size system 24) . Due to the very high concentration of polymer segments, the "single-site bond fluctuation model" proposed by Larson et al 25,26) and Carmesin et al 27) and the "vacancy diffusion algorithm" suggested by Lu et al 28) , which has been used by Lu and Yang 21) , have been applied here in order to perform the Monte Carlo simulation efficiently. The model and the corresponding microrelaxation modes are schematically depicted in Fig.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…1 of ref. 21) Chain configuration evolves during the course of the Monte Carlo simulation by attempting random displacements of a single vacancy site to the eight nearest neighbor site beads on the lattice. These attempted moves change the lengths of the bonds within the chain; chain connectivity is maintained by restricting the bond lengths to the values of 1 and 2 p .…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Considering that the polymer concentration is high, we adopted the 'single-site bond fluctuation' model proposed by Larson et al [19,20] and Carmesin et al [21] and the 'vacancy diffusion' algorithm suggested by Lu et al [22] to improve the Monte Carlo simulation efficiency. A schematic of the model and the corresponding microrelaxation modes can be found elsewhere [23]. The evolution of the chain configuration in the simulation was achieved by the random displacement of single vacancy site to its one of eight nearest neighboring sites on the lattice.…”
Section: Simulationmentioning
confidence: 99%